What Do Teachers Know About Student Burnout Symptoms During the COVID-19 Pandemic? - Katarzyna Tomaszek; Agnieszka Muchacka-Cymerman (Multidisciplinary Journal of School Education)
Research Objectives and Problems: The aim of this article is to analyze the phenomenon of student burnout in the context of the COVID-19 pandemic and examine the extent to which teachers can recognize burnout symptoms in students. The study considers both teachers’ and parents’ perspectives, highlighting discrepancies in their identification of symptoms.